Reflections on Avicenna's impact on medicine: his reach beyond the middle east - Zahra Aligabi (Greater Baltimore Medical Center, 2020)
Avicenna, to the west, and Ibn Sina to the East, is more than a historical figure often overlooked beyond his contributions to the Golden Age of Islam. While a deeper image of this multi-faceted individual can be cultivated by exploring his extensive contributions to the fields of medicine, science, philosophy, and pharmacology, his impact on medicine is often forgotten. However, it is important to shed light on the role of the 'Prince of Physicians' in the major advancements achieved in medicine today, especially with regards to the Western hemisphere. This report focuses on Avicenna's advancements in the medical field, and how there is more to the history of medicine than Hippocrates and the western authorities that dominate our accounts.